Uji Efektivitas Termitisida Nabati Terhadap Mortaliatas Rayap (Coptotermes curvinagthus Holmgren) (Isoptera : Rhinotermitidae) di Laboratorium The Effectiveness of Botanical Termiticides on Mortality of Termites (Coptotermes Curvinagthus Holmgren) (Isopte - Nova Kristina Hutabarat; Syahrial Oemry; Mukhtar Iskandar Pinem (Universitas Sumatera Utara, 2015)
This research aims to determine the effetiviness of Botanical termiticide tuba root (Derris elliptica(Roxb) Benth) and citronella (Cymbopogon nardus L) of mortality of termites (Coptotermescurvinagthus Holmgren) in laboratory. This method uses Randomized Complete Design with twofactor : the first factor was concentration of termiticide (Control, Soluble of tuba root 200 g/ L water,Soluble of tuba root 300 g/ L water, Soluble of tuba root 200 g / L water, Soluble of citronella 300 g / Lwater, Soluble of citronella of 200 g / L water) and second factors was application technique (feedingand spraying).The result showed that concentration and application technique of termiticidesignificantly effected the mortality of termites. The highest mortality (83,86%) on soluble of tuba root300 gr / water and the lowest ( 0 %) on control. Mortality of termites on feeding application (66,77%)was higher than spraying application (56.86%)Keywords: Botanical Termiticides , Coptotermes Curvinagthus Holmgren, Mortality